A Common Fixed Point Theorem for Nonlinear Quasi-Contractions on b-Metric Spaces with Application in Integral Equations. (29th September 2020) - Mitrović, Zoran D.; Aranđelović, Ivan D.; Mišić, Vesna; Dinmohammadi, Abdollah; Parvaneh, Vahid
Abstract : In this paper, we present a common fixed point result for a pair of mappings defined on a b-metric space, which satisfies quasi-contractive inequality with nonlinear comparison functions. An application in solving a class of integral equations will support our results.